2015
DOI: 10.1080/19393210.2015.1067649
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1in eggs and chicken livers by dispersive liquid–liquid microextraction and HPLC

Abstract: A rapid, low-cost and simple technique has been developed for the determination of aflatoxin B1 (AFB1) in eggs and livers using high-performance liquid chromatography (HPLC) with UV detection. In this study, the presence of AFB1 was investigated in 150 eggs and 50 chicken livers from the local market of Tabriz, Iran. AFB1 was extracted with a mixture of acetonitrile:water (80:20) and cleaned up by dispersive liquid-liquid microextraction which is a very economical, fast and sensitive method. AFB1 was quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…They reported that the amount of aflatoxin found in meatball samples was above the limit, and that of sausages was very close to the limit. Maktabi (22) reported that %72 of the liver samples and %58 of the egg samples were contaminated with AFB1 in the analysis of 150 eggs and 50 chickens by the HPLC method. Murad et al (23) collected 60 poultry samples from butcher shops in Sulaimani and analyzed AFB1 HPLC method.…”
Section: Aflatoxinsmentioning
confidence: 99%
“…They reported that the amount of aflatoxin found in meatball samples was above the limit, and that of sausages was very close to the limit. Maktabi (22) reported that %72 of the liver samples and %58 of the egg samples were contaminated with AFB1 in the analysis of 150 eggs and 50 chickens by the HPLC method. Murad et al (23) collected 60 poultry samples from butcher shops in Sulaimani and analyzed AFB1 HPLC method.…”
Section: Aflatoxinsmentioning
confidence: 99%
“…The comparison of the in-syringe VAEME-SFOD with other microextraction techniques [7][8][9]13,17,22] for the extraction, pre-concentration, and determination of AFs is shown in Table 3. As it is shown, the in-syringe VAEME-SFOD has lower LODs values than the other techniques.…”
Section: Comparison Of the Developed Technique With Other Microextracmentioning
confidence: 99%
“…Noteworthy, it is usual to these microextraction methods to be coupled with immunoaffinity column extraction as an additional step or to compare performance results among methods. Amirkhizi and coworkers used a dispersive liquid-liquid microextraction as a clean-up method before the quantitation of AFB 1 in eggs (n = 150) and chicken livers (n = 50) obtaining incidences of 72% and 58%, respectively [64]. A review by Spietelun and coworkers treat, in general, miniaturized analytical pretreatment options (e.g.…”
Section: Recent Approaches For the Extraction Of Aflatoxins From Feedsmentioning
confidence: 99%